Moznosti vyuzití hmotnostrí spektrometrie k subtypizaci kampylobakteru - Koláčková, Ivana; Štromerová, Nikola; Bardoň, Jan; Pudová, Vendula; Karpíšková, Renáta (Klinicka mikrobiologie a infekcni lekarstvi, 2015)
OBJECTIVES: Molecular epidemiology is a field that uses results of typing techniques to obtain information on detailed characterization of bacterial strains for determining the identity, similarity or difference in bacteria of the same genus, species or serotype. Nowadays, the most commonly used methods are based on monitoring differences in bacterial genotypes. However, most of these techniques are time-consuming and costly. A method increasingly used in routine microbiological testing is matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS), which is based on analysis of the bacterial proteome. It is mainly used for rapid and accurate classification of bacteria into genera and species. The aims were to assess the potential use of this method for typing of Campylobacter below the species level and to apply these results in epidemiological investigations. MATERIAL AND METHODS: The study comprised 39 strains of Campylobacter jejuni isolated from food (16) and humans (23). Macrorestriction fragment profiling by pulsed-field gel electrophoresis (PFGE) and simultaneous protein profile analysis using MALDI-TOF MS were performed for all tested strains. RESULTS: Similar pulse profiles were found among isolates originating from the same outbreak or repeatedly collected from a single patient. The same pulse profiles were also detected in strains of unknown relationship but sharing the same place of origin and year of isolation. The comparison of dendrograms from both analyses showed that strains identified as identical by PFGE appeared in the same subgroups in dendrograms obtained by MALDI-TOF MS, the only exception being isolates repeatedly collected from a single patient. CONCLUSION: The results suggest that confirmation of the identity or similarity of strains in accordance with the established epidemiological facts has not been clearly demonstrated using MALDI-TOF MS.
Keywords: Food Microbiology; Campylobacter Infections; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; pulzní gelová elektroforéza; Humans; kampylobakterové infekce; Electrophoresis, Gel, Pulsed-Field; Campylobacter jejuni; techniky typizace bakterií; potravinářská mikrobiologie; Bacterial Typing Techniques; lidé